Functional asymmetry in sport - Sychev, V. S.; Davydova, S. S.; Kashkarov, V. A. (Theory and Practice of Physical Culture, 2017)
High sports achievements require all components of the athletes` body functional fitness to be taken into account. Functional asymmetry of the brain is one of the most important determinants of human capabilities in motor task solution. There is a considerable body of evidence to suggest the role of various asymmetries in sports activities, their peculiar dynamics in the training process. However, a number of key issues of motor and sensory asymmetries remain unclear so far, and their resolution requires further research and discussion.